2006
DOI: 10.1175/jcli3934.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variation of the Tropical Cyclone Activity over the Western North Pacific

Abstract: An effort was made to search for relationships between interannual variations of population, lifetime, genesis locations, and intensity of named typhoons and numbered tropical depressions in the western North Pacific during the 1979-2002 period. To support this research task, climatological relationships of tropical cyclone characteristics were also investigated for these cyclones. Major findings of this study are summarized as follows:1) Climatology: Measured by the intensity scale of the Japan Meteorological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
85
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 15 publications
14
85
0
2
Order By: Relevance
“…Fig. 4b), however, manifests a very different picture, featuring a much more widespread TC activity pattern due to the inclusion of TC duration and intensity within and are consistent with the findings of Chen et al (2006). The ACE pattern (see Fig.…”
Section: Seasonal Cyclesupporting
confidence: 73%
See 2 more Smart Citations
“…Fig. 4b), however, manifests a very different picture, featuring a much more widespread TC activity pattern due to the inclusion of TC duration and intensity within and are consistent with the findings of Chen et al (2006). The ACE pattern (see Fig.…”
Section: Seasonal Cyclesupporting
confidence: 73%
“…5a), positive anomalies dominate the southeastern part of the WNP; while negative anomalies dictate the northwestern part. This implies that the major birthplace of TC would be shifted southeastward during an El Niño year (Chen et al 1998;Chia and Ropelewski 2002;Chen et al 2006). For TCD, ACE, RACE, PDI and RPDI anomalies (see Figs.…”
Section: Contrast In Climate Variabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies also noticed that the interannual changes of TC activity in the WNP are associated with a longitudinal shift in the upward and downward branches of the Walker Circulation during the warm phase of ENSO (e.g., Chan 1985;Wu and Lau 1992). Lander (1994) and Chen et al (1998) attributed the eastward shift of the genesis region to an eastward extension of the monsoon trough in the WNP since most TCs form in the shear zone between the monsoonal westerlies and the trade easterlies (Sadler 1967;Ritchie and Holland 1999). Most of the previous studies on interannual variability of the WNP TCs have focused on the El Niño developing years.…”
Section: Introductionmentioning
confidence: 91%
“…The interannual variations of tropical cyclone (TC) activity in the western North Pacific (WNP) have been extensively investigated in the past 2-3 decades (Chan 1985(Chan , 2000Lander 1994;Chen et al 1998;Wang and Chan 2002;Chia and Ropelewski 2002;Chu 2004;Camargo and Sobel 2005;Camargo et al 2007). Chan (1985) first examined the relationship between the WNP TC activity and the El Niño-Southern Oscillation (ENSO) and found that the spectra of both TC annual counts and ENSO Index peak in the 3-3.5 year frequency band.…”
Section: Introductionmentioning
confidence: 99%